EMPOWERMENT STRATEGY OF BAROKAH FOOD MSMEs GROUP THROUGH LPEM BAZNAS MUSTAHIK ENTREPRENEURSHIP PROGRAMME IN DEPOK CITY - Chairani, Hanifah; Muhtadi, Muhtadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
BAZNAS Mustahik Economic Empowerment Agency is a productive zakat management and utilisation institution. This institution, through the Mustahik Entrepreneur empowerment programme, empowers and distributes zakat funds to mustahik MSMEs actors who have the potential to develop their businesses. The Mustahik Entrepreneur programme acts as a tool for productive mustahik to develop into muzakki. This research aims to explain LPEM's strategy in empowering mustahik groups, the stages of empowerment, and the inhibiting and supporting factors of the empowerment programme of the Barokah Food MSMEs group of the Mustahik Entrepreneur Programme of LPEM BAZNAS. This research uses a descriptive qualitative approach. Data collection techniques through observation, interviews, and documentation as well as purposive sampling techniques in selecting research informants. Data analysis through three flows, namely data reduction. Presentation of data and conclusion drawing. The results of the research that economic empowerment in the Barokah Food MSMEs group are: 1) Capital assistance, not just direct funds but also business tools and materials; 2) Improving skills, mustahiks are accompanied and coached to improve skills and develop businesses; 3) Sustainable empowerment. The conclusion is that the empowerment of the Barokah Food MSMEs group through the Mustahik Entrepreneur Programme has increased mustahik income, developed businesses while increasing mustahik knowledge and skills.